2016
DOI: 10.1007/s00706-016-1822-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and antioxidant activity of Zn2+ and Cu2+ coordinated polyhydroxychalcone complexes

Abstract: Four new metal complexes [Cu(ISO)2], [Cu(BUT)2] and [Zn(ISO)2], [Zn(BUT)2] of the polyhydroxychalcones (isoliquiritigenin and butein) are synthesized, structurally characterized and their antioxidant activity is investigated. The formation of the complexes [Cu(ISO)2] and [Zn(ISO)2] is followed by Job’s plot using NMR titration. The resulting compounds are characterized by mass spectrometry, IR spectroscopy, and elemental analysis. Studies on the radical scavenging activity are performed using DPPH as substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 46 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…The obtained results were in agreement with several works reported in the literature with regards to the antioxidant potential of metal complexes. In a recent study, Sulpizio et al . have reported that the metal complexes [Cu (ISO) 2 ] and [Zn (ISO) 2 ] show 72 and 88% inhibition of the DPPH radical.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results were in agreement with several works reported in the literature with regards to the antioxidant potential of metal complexes. In a recent study, Sulpizio et al . have reported that the metal complexes [Cu (ISO) 2 ] and [Zn (ISO) 2 ] show 72 and 88% inhibition of the DPPH radical.…”
Section: Resultsmentioning
confidence: 99%
“…The M-O band for Zn(II) was observed at 500 cm -1 . Chiara Sulpizio assigned that, [9] Zn +2 do not show any significant shift compared to the free ligand. While the Zn +2 complexes show a shift of C=0 stretching mode from 1630 to 1610 cm -1 indicating coordination of carbonyl oxygen to a metal ion.…”
Section: IIImentioning
confidence: 98%
“…The percentage of inhibition (I%) of free radical production by DPPH was calculated using the formula, (I%) = [(A0 -Ac)/A0]  100 where A0 and Ac are the absorbance in the absence and presence of the metal complexes respectively. [32]…”
Section: Antioxidant Activitymentioning
confidence: 99%